Exponentially growing osteosarcoma of mandible with acromegaly. Issue 6 (16th February 2016) - Choi, Nayeon; Kim, Seokhwi; Cho, Jungkyu; Kim, Byung Kil; Cho, Young Sang; Jang, Jeon Yeob; Baek, Chung‐Hwan
ABSTRACT: Background: Osteosarcoma of the head and neck is aggressive malignancy that might be affected by growth hormone. The purpose of this study was to demonstrate an unusual case of osteosarcoma with acromegaly. Methods and Results: This case is about a 39‐year‐old woman with an osteosarcoma of the mandible, who had a history of exponential tumor growth in spite of chemotherapy at another hospital. She transferred to Samsung Medical Center and underwent a wide resection of tumor and free flap reconstruction. During postoperative care, a brain MRI and hormonal test revealed a growth hormone‐secreting pituitary adenoma, and then a transsphenoidal approach pituitary tumor removal was performed. Immunohistochemistry of the osteosarcoma indicated positive for insulin‐like growth factor (IGF)−2 and somatostatin receptor. Conclusion: This study proved the IGF‐2 and somatostatin receptor from the osteosarcoma of the patient with acromegaly, and this could explain that the growth hormone secreting from the pituitary adenoma might be a risk factor of therapeutic intractability and growth acceleration of osteosarcoma. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2432–E2436, 2016